Constructing the check-in: Reflections on photo-taking among Foursquare users. Issue 2 (June 2019) - Wilken, Rowan; Humphreys, Lee
In this article, we explore the social construction of geomedia in relation to mobile photo-taking. The article draws from a study of location-sensitive mobile social networking and search and recommendation service Foursquare in Melbourne and New York City. The study utilized photo elicitation techniques, with each participant asked to provide photographs they associated with their own Foursquare check-ins, accompanied by written responses to questions designed to encourage them to reflect upon their motivations for recording and uploading each image. What emerged from our analysis of how participants discussed the construction of their Foursquare check-ins, were certain consistencies with the findings of prior work on Foursquare (e.g. to register a new venue or a nice meal, as part of exercises in self-expression, and to record memory traces). Strikingly, though, we also noticed something subtly yet significantly different in relation to photo use. Many of the submitted images and accompanying explanations revealed a particular sensitivity toward the local and the familiar, and a desire to capture "a mood, a feeling"—an "ordinary affect." In light of this, in this article we are interested in the tension that exists between designed or intended uses of Foursquare, the social appropriation and shaping that is undertaken by Foursquare's end-users, and the technological and strategic business adjustments that are undertaken by Foursquare in response.